A review of transfusion reaction reports for the year 2008 - Ismail, Rusmawati; A.Talib, Norlelawati; Mohd Shahid, Salman; Ramachandran, Kalavathy; Muhammad, Siti Aeshah @ Naznin (2009)
Blood transfusion reaction is defined as any adverse manifestation following transfusion of blood or blood products. The symptoms of transfusion reaction range from a mild allergy reaction to a life threatening anaphylactic or haemolytic reaction. The National Haemovigilance programme requires all adverse reactions to be investigated and reported. For all cases of blood transfusion reactions, blood and urine samples should be collected for investigation against all possible causes of transfusion reactions. The samples together with the remaining blood bag and completed transfusion reaction forms are to be sent to transfusion laboratory. In addition, blood culture taken from the remaining bag and patient’s blood are also part of the transfusion reactions work up.